The Development of Augmented Reality (Ar) Based Science Learning Media at MI Yaa Bunayya - Mukti, Fajar Dwi (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2022)
This study aims to produce an Augmented Reality (AR)-based learning media in the science field at MI Yaa Bunayya. The development method in this study uses a modified Thiagarajan 4D model with three stages (Define, Design, and Develop). The Augmented Reality (AR) learning media, later named the SANDIR Application, was assessed by the reviewer and 10 class V students of MI Yaa Bunayya to find student responses. The instrument used is a checklist questionnaire. The data obtained is in the form of qualitative data which is converted into quantitative, analyzed descriptively to determine the quality of the product. The results showed that the SANDIR Application learning media for science subjects that had been developed was based on reviewers' assessments with an average score of 33.7, classified as very good (SB). SANDIR application learning media based on student responses has a percentage of 99.13 with a positive value category in helping students' understanding while learning and is included in the very good quality category. Based on the data acquisition results, the SANDIR Application learning media is in accordance with the cognitive development of elementary school-aged children and is suitable for use as a learning resource for fifth grade students of elementary school.